HIGHER ORDER THINGKING SKILLS SISWA SMP PADA MATERI ARITMATIKA SOSIAL - Yesi Imas Sri Rahayu; Siti Chotimah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
The aims of this research is to describe students' higher order thinking skills in solving social arithmetic problems. The method in this study is a qualitative descriptive method. The data collection technique is by giving higher order thinking skill test questions to students. Then further analyze students' answers and assess students' higher order thinking skills in social arithmetic material. The object of this research is 20 students in a private junior high school in West Bandung Regency. The instrument used is a test about social arithmetic material with the type of higher order thinking skill. The results of the study prove that students still experience problems in solving problems on Higher Order Thinking Skill questions at 3 levels of Bloom's taxonomy, namely: analyzing (C4); evaluate (C5); and create (C6). This is evidenced by the results of the students' higher order thinking skills which show that no one gets the very good category, most of the students only get the sufficient category. The factors that make the problem experience problems are (1) Not being able to analyze; (2) Unable to refute, evaluate or support an idea and cannot find reasons to support the answers obtained; (3) Unable to provide solutions to problems and integrate information into correct steps.